Customer orientation, service quality and customer satisfaction interplay in the banking sector: An emerging market perspective - Eric Gonu; Paul Mensah Agyei; Opoku Kofi Richard; Mary Asare-Larbi (Cogent Business & Management, 2023)
Customer satisfaction is at the heart of any successful business entity. The influence of service quality on the role of customer orientation in achieving greater customer satisfaction in the banking industry from the perspective of customers has not received the required attention in the marketing literature. This study sought to respond to the question of whether service quality could influence the effect of customer orientation on customer satisfaction. The study adopts a quantitative research approach with a descriptive survey design. With the aid of PLS-SEM, data from 391 commercial bank customers was analysed. It was identified that, within the banking industry, customer orientation is a key predictor of customer satisfaction. Customer satisfaction would improve when service quality improves, and service quality plays a partial role in the relationship between customer orientation and service quality. The study recommends that policymakers develop comprehensive policies and also direct the management of commercial banks to develop customer orientation programmes.
Keywords: 650; banking; customer orientation; Customer satisfaction; emerging market; service quality